Clinical features of external genital endometriosis - Bohomolova, O. A. (Запорізький державний медичний університет, 2018)
Introduction: Despite the long-term studies of endometriosis, there is little known reliable information about the etiology and pathogenesis of the disease. The problem of treatment of external genital endometriosis remains relevant in connection with the increase in its frequency and the presence of clinical forms. The aim of our study was to investigate the clinical features of external genital endometriosis of varying degrees of activity. Materials and methods: a comparative analysis of the clinical course, duration of the disease, condition of the reproductive system, age of patients in 55 women with external genital endometriosis of varying severity (I-IV) was carried out. A complete clinical and laboratory examination of patients included clinical-anamnestic, hormonal, ultrasound, roentgenologic, endoscopic examination. Statistical processing and final evaluation of the data was carried out using the Microsoft Excel program.
Keywords: тези доповідей